2007
DOI: 10.1007/s00531-006-0157-8
|View full text |Cite
|
Sign up to set email alerts
|

Plumbotectonic aspects of polymetallic vein mineralization in Paleozoic sediments and Proterozoic basement of Moravia (Czech Republic)

Abstract: A regional isotopic study of Pb and S in hydrothermal galenas and U-Pb and S in potential source rocks was carried out for part of Moravia, Czech Republic. Two major generations of veins, (syn-) Variscan and post-Variscan, are defined based on the Pb-isotope system together with structural constraints (local structures and regional trends). The Pb-isotopic compositions of galena plot in two distinct populations with outliers in 206 Pb/ 204 Pb-207 Pb/ 204 Pb space. Galena from veins hosted in greywackes provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 52 publications
1
0
0
1
Order By: Relevance
“…The idea of a local REY source is also supported by earlier findings of Slobodník et al (2008) who reported a good agreement between Pb and S isotopes in galena in post-Variscan hydrothermal veins and time-integrated Pb isotope ratios and S isotopes in the host rocks. They suggested that the source of lead and sulphur was mostly in the Carboniferous siliciclastic sediments.…”
Section: Source Rocks and Minerals Of Reysupporting
confidence: 72%
“…The idea of a local REY source is also supported by earlier findings of Slobodník et al (2008) who reported a good agreement between Pb and S isotopes in galena in post-Variscan hydrothermal veins and time-integrated Pb isotope ratios and S isotopes in the host rocks. They suggested that the source of lead and sulphur was mostly in the Carboniferous siliciclastic sediments.…”
Section: Source Rocks and Minerals Of Reysupporting
confidence: 72%
“…De nombreux travaux de plombotectonique ont été réalisés depuis lors. Dans la plupart des provinces plombifères du monde, le plomb est d'origine crustale : c'est le cas notamment dans les Calédonides scandinaves (Billström et al, 1997), les Variscides européennes (Marcoux et Jébrak, 1987 ;Bau et al, 2003 ;Slobodník et al, 2008), la partie orientale de la chaîne d'Asie centrale (Wang et al, 2020) et jusqu'au Japon (Doe et Zartman, 1982). Dans ce contexte crustal, Sawkins (1989) a montré que le plomb des gisements géants des bassins protérozoïques postérieurs à 1,8 Ga aurait été hérité du magmatisme anorogénique d'âge protérozoïque moyen, un réservoir primaire riche en feldspaths et anomal en plomb.…”
Section: Introductionunclassified